2022
DOI: 10.1093/chromsci/bmab143
|View full text |Cite
|
Sign up to set email alerts
|

Headspace-Low Water Absorption Trap Technique: Analysis of Low-Abundance Volatile Compounds from Fresh Artemisia Annua L. with GC–MS

Abstract: Conventional headspace (HS) method could not meet the requirement of analyzing low-abundance volatile compounds in high water content samples. A HS-low water absorption trap technique coupled with gas chromatography–mass spectrometry was introduced to remove the large amount of water vapor; therefore, the low-abundance volatile compounds could be detected with better analytical sensitivity. With this method, a total of 81 volatile compounds were identified from fresh Artemisia annua L. by mass spectral library… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…It has been reported that the AALE was found to contain steroids and terpenoids, with several phyto-constituents screened by the GC-MS method [30]. For instance, 2,4,6-trimethyl-1,3,6-heptatriene was detected as a bioactive agent in AALE, which agreed with Liu et al (2022), who detected the same constituent as the main component in AALE [31]. Interestingly, in this study, three natural sesquiterpenes, βcaryophyllenea, α-Santonin, and spathulenol, were abundantly identified in AALE, which provide several biological activities, including antioxidant, antimicrobial, anticarcinogenic, and anti-inflammatory effects [32][33][34].…”
Section: Discussionsupporting
confidence: 81%
“…It has been reported that the AALE was found to contain steroids and terpenoids, with several phyto-constituents screened by the GC-MS method [30]. For instance, 2,4,6-trimethyl-1,3,6-heptatriene was detected as a bioactive agent in AALE, which agreed with Liu et al (2022), who detected the same constituent as the main component in AALE [31]. Interestingly, in this study, three natural sesquiterpenes, βcaryophyllenea, α-Santonin, and spathulenol, were abundantly identified in AALE, which provide several biological activities, including antioxidant, antimicrobial, anticarcinogenic, and anti-inflammatory effects [32][33][34].…”
Section: Discussionsupporting
confidence: 81%